Synthesis and anticonvulsant activity of amino acid-derived sulfamides - Gavernet, Luciana (2009)
Sulfamides are promising functions for the design of new antiepileptic drugs (Bioorg. Med. Chem. 2007, 15, 1556-1567; 5604-5614). Following previous research in this line, a set of amino acid-derived sulfamides has been designed, synthesized, and tested as new anticonvulsant compounds. The experimental data confirmed the ability of some of the structures to suppress the convulsions originated by the electrical seizure (MES test) at low doses (100 mg/kg).